THE CURRENT STATE OF COMMUNICATION SKILLS OF NURSES IN CLINICAL DEPARTMENTS OF HO CHI MINH CITY EYE HOSPITAL PERIOD 2025-2026 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current state of communication skills of nurses working in clinical departments at Ho Chi Minh city Eye Hospital period 2025-2026.Research methods: A cross-sectional descriptive study involving 250 inpatients was conducted from December 2025 to March 2026. Data were collected utilizing AIDET-based questionnaires and analyzed using SPSS 20.0 software.Results: The percentage of nurses performing well in general communication skills was 90%, including: establishing relationships (80.4%); self-introduction (89.2%); providing time information (80%); explaining procedures (82%); and thanking patients (84%). However, 10% of nurses still did not achieve a good level, and over 50% did not fully meet all 5 AIDET criteria.Conclusion: While nurses generally exhibit adequate communication skills, adherence across the five AIDET domains is inconsistent. Enhanced training and targeted supervision are required to standardize and optimize patient-provider communication.
Keywords: Nursing, communication, AIDET, patient, hospital.